Decolonizing Art Book Fairs : Publishing Practices from the South(s) (Afrikaada, Paris; Miss Read, Berlin; Mosaiques, Yaounde, 2021)
Can we decolonize art book fairs? Can we decentralize knowledge and deconstruct privilege in our contexts? Decolonizing Art Book Fairs aims to rethink through the existing and speculative frameworks of organizational practice in the art book fairs. This workbook attempts to introduce new narratives and help deconstruct the frontiers between north(s) and south(s), putting an emphasis on practitioners and initiatives from the African continent and African diaspora. A workbook with (primarily newly commissioned) texts and interviews. Contributors: Jean-Claude Awono, Yaiza Camps, Chayet Chienin, Chimurenga, Renata Felinto, Wanjeri Gakuru, Moritz Grunke, Aryan Kaganof, Sharlene Khan, Grada Kilomba, Carla Lever, Fouad Asfour, Dzekashu MacViban, Gladys Mendia, James Murua, Tinashe Mushakavanhu, Simon Najmi, Bonaventure Soh Bejeng Ndikung, Monica Nkodo, O Menelick 2Ato, Pascale Obolo, Michalis Pichler, Mario Pissarra, Sergio Raimundo, Djimeli Raoul, Flurina Rothenberger, Bienvenu Sene, Bisi Silva, Kwanele Sosibo, Parfait Tabapsi, Louise Umutoni, Zaman Books & Curating
English
Keywords: Art book fairs. Art book publishers. Art book publishing practices; NX1-260 Arts in general. General